Unlocking Financial Insights: My Journey at J.B. Chemicals & Pharmaceuticals Ltd. - Kabra, Jheel (ATLAS SkillTech University, 2025)
J.B. Chemicals & Pharmaceuticals Limited (JBCPL) is a leading Indian pharmaceutical company with a global presence. Founded in 1976, the company has grown to become one of the fastest-growing pharmaceutical companies in India, with a strong focus on innovation, quality, and customer satisfaction. JBCPL is headquartered in Mumbai, Maharashtra, and has manufacturing facilities across various locations in India.
Project Report on Unlocking Financial Insights: My Journey at J.B. Chemicals & Pharmaceuticals Ltd. (2023-2025) Under the Guidance of Prof. Sadaf Hashmi
Keywords: pharmaceutical; innovation